Implementation of Machine Learning Techniques for Big Mart Sales Forecast Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The sales data for each individual item is now tracked by supermarket run-centers, Big Marts, in order to forecast possible consumer demand and revise inventory control. By mining the data store of the data warehouse, wide-ranging trends as well as anomalies are frequently found. The generated data may be utilised by merchants such as Big Mart that employ a number of machine learning techniques in order to forecast forthcoming sales volume. A prediction algorithm was developed to estimate the sales of an organisation like Big-Mart utilising Xgboost, Linear regression, Polynomial regression, also Ridge regression methodologies. It was shown that the model beats other models.